THE WRITTEN REPORT IN ACCOUNTING SYSTEMS. - Allen, C. E. (The Accounting Review, 1935)
Abstract In the teaching of accounting systems one finds that it is often difficult for the student to see the practical application of the accounting theories discussed in the classroom. No doubt this is due largely to the lack of practical experience on the part of the student. Some schools overcome this handicap by arranging for part time work in the accounting departments of local business concerns. Other schools find this arrangement impossible, due to the scarcity of such business concerns or the general policies of the college or university. This lack of experience may be at least partially overcome by means of the written report, which may be used to supplement the course in accounting systems. In this report the undergraduate may select a business concern either in the college community or elsewhere, usually near his own home, and make a first hand study of the accounting system of that business. The outline is given to the student early in the semester and soon afterwards he is asked to name the kind of business in which he is interested and on which he would like to make a report.